Kinerja Keuangan Perusahaan Entertainment Korea Selatan, Manakah yang Terbaik? - Nispatussolihah; Hudaya, Robith (Fakultas Ekonomi dan Bisnis Unram, 2025)
The financial performance of South Korean entertainment companies amidst the great enthusiasm of the global community including Indonesia towards the Hallyu or Korean Wave phenomenon is an interesting to study. So, this study aims to analyze and compare the financial performance of several South Korean entertainment companies by measuring the liquidity, solvency, and profitability ratios of the company. This study is a descriptive study using a quantitative approach. The study was conducted using 4 South Korean entertainment companies with the highest market capitalization as research samples. Based on the results of the study, it can be concluded that financial performance when viewed based on the liquidity ratio can be sorted from the best to the lowest are JYP, HYBE, YG, and finally SM. Furthermore, based on the solvency ratio, the best is YG, then JYP, third SM, and finally HYBE. Then when viewed based on the profitability ratio, the best financial performance is owned by JYP, second YG, third SM, and HYBE in the last position. Overall, it can be seen that the best financial performance is owned by JYP Entertainment. Then YG Entertainment's financial performance shows quite good results. Meanwhile, SM Entertainment. and HYBE have less good financial conditions.